(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Biology originated with the concept of adjustment. In biology, the term commonly preferred an idea that was a corner stone in the evaluation theory of Darwin in adjustment. The psychologist borrowed the biological idea of adaptation and called it adjustment. Behaviour is defined in psychology as adjustment to requirements or conditions. The purpose of the study was to compare and investigate the adjustment between amateur golfers and caddie turned amateur golfers. To participate in the present analysis, two hundred (200) male golfers aged 18 to 24 years were sampled randomly. They were further split into two categories, comprising one hundred (n=100) amateur golfers and one hundred (n=100) amateur golfers. Sinha Singh’s AICS (1980) was employed to measure five dimensions of adjustment i.e., home, health, social, emotional, and educational and total adjustment. For analysing the data, statistical method was applied, results showed that the home, health, social, emotional, and educational dimensions, there was a significant difference in the test scores of amateur golfers and caddie turned amateur golfers. But caddie turned amateur golfers were significantly good in overall adjustment pattern to the amateur golfers.